2016
DOI: 10.1002/bmc.3663
|View full text |Cite
|
Sign up to set email alerts
|

An HPLC‐ECD method for monoamines and metabolites quantification in cuttlefish (cephalopod) brain tissue

Abstract: The cuttlefish belongs to the mollusk class Cephalopoda, considered as the most advanced marine invertebrates and thus widely used as models to study the biology of complex behaviors and cognition, as well as their related neurochemical mechanisms. Surprisingly, methods to quantify the biogenic monoamines and their metabolites in cuttlefish brain remain sparse and measure a limited number of analytes. This work aims to validate an HPLC-ECD method for the simultaneous quantification of dopamine, serotonin, nore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…The found LOQs are similar to or better than the ones reported with other chromatographic methods using electrochemical detection, where LOQs of 3 nM up to 70 nM were obtained [9,10,25]. The LOQs observed in the current study were significantly better than LOQs observed with LC-MS/MS methods (app.…”
Section: Linearity and Loqsupporting
confidence: 85%
See 1 more Smart Citation
“…The found LOQs are similar to or better than the ones reported with other chromatographic methods using electrochemical detection, where LOQs of 3 nM up to 70 nM were obtained [9,10,25]. The LOQs observed in the current study were significantly better than LOQs observed with LC-MS/MS methods (app.…”
Section: Linearity and Loqsupporting
confidence: 85%
“…MHPG was observed to be the most unstable analyte at 4°C in brain homogenate, as also reported in earlier stability studies [9,25].…”
Section: Stability Studysupporting
confidence: 64%
“…A recent HPLC‐ECD methodology has reported quantification limits adequate for discrete brain region analysis of DA, DOPAC and 5‐hydroxyindolacetic acid (5‐HIAA) levels; however, determination of DA turnover ([DOPAC + HVA]/[DA]) within the SNpc and VTA regions would be problematic given the reported calibration range and LLOQ for HVA (~2.8 ng/mL after 5 μL sample volume injection; Nguyen, Aerts, Van Dam, & De Deyn, ). Moreover, methods which report very sensitive limits of detection (fmol to pmol range) are often found accompanied by the use of damaging high electrode potentials (> 700 mV; Bidel et al, ; Parrot et al, ; Vaarmann, Kask, & Mäeorg, ), the inability to measure all monoamines and metabolites simultaneously (Heidbreder et al, ; Hubbard et al, ) or long analytical run times (>25 min; Kumarathasan & Vincent, ; Nguyen et al, ; Unceta et al, ; Van Dam, Vermeiren, Aerts, & De Deyn, ). Shorter‐length columns and ultra‐high‐pressure liquid chromatography (UHPLC) systems are commonly employed to decrease analysis time (Farthing et al, ; Parrot et al, ; Reinhoud, Brouwer, van Heerwaarden, & Korte‐Bouws, ); however, it has been reported that chromatographic efficiency in complex matrices, particularly during isocratic elution using electrochemical detection, is often reduced as column length decreases (Bicker et al, ; Mutton, ; Nguyen, Guillarme, Rudaz, & Veuthey, ).…”
Section: Introductionmentioning
confidence: 99%
“…Of these previously developed HPLC‐ECD methodologies, measurements were achieved in larger brain regions, including the frontal cortex (FCtx), hippocampus (HIP), striatum (STR) and nucleus accumbens (NAc) but were not assessed in smaller regions, such as the dopaminergic SNpc and VTA, and LLOQs (signal‐to‐noise ratio ≥ 10) were not reported for these assays. In addition, these methodologies require ultrafiltration of prepared samples prior to analysis and are thus susceptible to analyte recovery issues (Bidel et al, ; Donzanti & Yamamoto, ; Saito, Murai, Abe, Masuda, & Itoh, ).…”
Section: Introductionmentioning
confidence: 99%
“…ECD is also much more specific for the monoamines than MS detectors. Therefore, although in recent decades several other detectors have been tested for the quantification of such derivatives, high-performance liquid chromatography (HPLC) with ECD is still considered one of the best choices, indicated by the high number of reports (Allen, Rednour, Shepard, & Pond, 2017;Bidel et al, 2016;Birbeck & Mathews, 2013;Ferry, Gifu, Sandu, Denoroy, & Parrot, 2014;Ganesana, Lee, Wang, & Venton, 2017;Nguyen, Aerts, Van Dam, & De Deyn, 2010;Parrot, Neuzeret, & Denoroy, 2011;Schou-Pedersen, Hansen, Tveden-Nyborg, & Lykkesfeldt, 2016;Smith, Schwartz, & Lucot, 2013;Tsunoda, 2006).…”
Section: Introductionmentioning
confidence: 99%